Dividend policy and stock price volatility of industrial products firms in Malaysia - Zainudin, Rozaimah; Mahdzan, Nurul Shahnaz; Yet, Chee Hong (Elsevier, 2018)
Purpose: The purpose of this paper is to analyse the relationship between stock price volatility (SPV) and dividend policy of industrial products firms listed on Bursa Malaysia. Design/methodology/approach: The sample comprises 166 industrial products public-listed firms covering a time span from year 2003 to 2012. Using Baskin’s framework, firm’s SPV is related to dividend payout, controlling for earnings volatility, firm size, leverage and growth of assets. Further, the impact of the global financial crisis on the relationship between SPV and the tested variables is examined. Findings: Earning volatility significantly explains SPV of industrial product firms during the crisis period, while dividend payout ratio (PR) predominantly influences volatility during pre- and post-crisis sub-periods. The empirical results indicate that dividend policy is a strong predictor of SPV of industrial products firms in Malaysia, particularly during the post-crisis period. Originality/value: The paper explores the firm’s SPV and dividend policy for a new set of data focussing on industrial products firms listed on the Malaysian Stock Exchange.